Timing of Primary PCI and Mortality in Acute Myocardial Infarction: Impact of Door to Balloon Time - Ullah, Ikram; Khan, Muhammad Idrees; Umar Farooq; Orakzai, Muhammad Hafeez; Abid Ullah; Ahmad, Sohail (Indus Journal of Bioscience Research, 2024)
Objective: This study aimed to evaluate the impact of door-to-balloon (DTB) time on mortality in patients with ST-segment elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI) at Hayatabad Medical Complex, Peshawar. Methodology: A prospective cohort study was conducted with 400 patients divided into two DTB time groups: "<60 minutes" and "60-90 minutes." Patient data, including age, DTB time, and mortality outcomes, were collected over 12 months (April 2022 to March 2023). Statistical analysis involved descriptive summaries and chi-square tests to assess associations between DTB time and mortality, using a p-value of <0.05 for significance. Results: Mortality rates were slightly higher in the "60-90 minutes" group (6.1%) compared to the "<60 minutes" group (5.3%); however, chi-square analysis showed no statistically significant association between DTB time and mortality (\( χ^2 = 0.07 \), \( p = 0.7849 \)). Age distribution was similar across groups, with no meaningful impact on mortality outcomes. The findings indicate that DTB time alone may not be a sufficient predictor of mortality in this cohort, emphasizing the need for a broader focus on total ischemic time and pre-hospital care. Conclusion: This study suggests that reducing DTB time alone may not significantly affect mortality in STEMI patients, underscoring the need for systemic improvements in pre-hospital and total ischemic time management to optimize patient outcomes.